2017
DOI: 10.1016/j.yebeh.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Health service provision for people with epilepsy in sub-Saharan Africa: A situational review

Abstract: We attempted to provide a 'snapshot' of epilepsy care services in SSA. The successes achieved in some of the centers are due to the use of existing primary health-care systems and employing non-physician health-care personnel. The true picture of epilepsy care coverage is not apparent due to the lack of data and proper health system structure in most parts of SSA. As more individuals begin to receive care, the long-term funding for epilepsy care in African countries will depend on the commitment of their respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 88 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…29 Further improvement can be made with continued training, as delivery of neurologic care through primary health providers is one of the main models of successful care in Africa. 30 Ancillary resources for patients with neurologic disorders vary substantially by country. In a study conducted by the World Health Organization (WHO), 29 only 56 countries responded to questions regarding supportive neurologic services, including neuroradiology, physical therapy, occupational therapy, and speech therapy.…”
Section: Care Delivery For Neurologic Disorders In Resource-limited Smentioning
confidence: 99%
See 3 more Smart Citations
“…29 Further improvement can be made with continued training, as delivery of neurologic care through primary health providers is one of the main models of successful care in Africa. 30 Ancillary resources for patients with neurologic disorders vary substantially by country. In a study conducted by the World Health Organization (WHO), 29 only 56 countries responded to questions regarding supportive neurologic services, including neuroradiology, physical therapy, occupational therapy, and speech therapy.…”
Section: Care Delivery For Neurologic Disorders In Resource-limited Smentioning
confidence: 99%
“…58 While in high-income countries, there is a growing ability to determine the etiology of childhood epilepsy, with a particular attention to genetic and metabolic syndromes and to target treatment to specific epileptic disorders, the diagnostic and therapeutic possibilities in most LMICs remain limited. 30,53,54 In most resource-limited settings, there is a paucity of specialized medical personnel and limited availability of EEG, laboratory, and neuroimaging services. 23,24,26,37,46 The same disparity between high-and low-income countries applies to access to antiseizure drugs (ASDs).…”
Section: Specific Diseases Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most important factors for the high surgical treatment gap are the lack of organized structured care, lack of infrastructure, shortage of specialists and the cost of surgery [21,[23][24][25]. A recent review observed that barriers to epilepsy surgery are perpetuated by the uncertainty portrayed by medical practitioners towards surgical treatments, reflecting the knowledge gap, which may be more pervasive in LMIC [26].…”
Section: Introductionmentioning
confidence: 99%